(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Objective: To evaluate the complications of laparoscopic cholecystectomy in the symptomatic cholelithiasis and other benign gall bladder diseases. Methods: This descriptive observational study was carried out at CMH Dhaka and CMH Jashore from March 2016 to Jun 2022, to evaluate the frequency and outcome of management of all the complications in laparoscopic cholecystectomy. A total of 1425 patients of laparoscopic cholecystectomy were included in this study. Patients were followed up for a period of three months after operation. The complications in laparoscopic cholecystectomy observed in this study were divided into (i) Access related (ii) Intraoperative (biliary and extrabiliary) and (iii) Postoperative. Results: The incidence of access-related, intraoperative or procedure-related biliary, extrabiliary and postoperative complications were 3.64%, 2.95%, 4.98% and 1.96% respectively. Access related complications were extraperitoneal insufflations 1.40%, port site bleeding 1.19%, small bowel laceration 0.21% and transverse colon injury 0.07%.Procedural biliary complications included common bile duct (CBD) injury 0.14%, common hepatic duct (CHD) injury 0.07% and iatrogenic gall bladder perforation with bile leakage 2.74%. Procedural extrabiliary complications were Liver injury 0.56%, duodenal perforation 0.07%, colon perforation 0.07%, bleeding through cystic artery 0.49% and bleeding from gall bladder fossa 1.12%. Two colonic perforations and one duodenal perforation were the major complications encountered in this series. Two colonic perforations required conversion to open procedure but duodenal perforation was managed laparoscopically by intracorporeal suturing. Total nine (0.63%) patients required conversion to open procedure. Postoperative complications included port site infection (PSI) 1.05%, port site hernia 0.56%, major sepsis 0.14% and ischemic stroke 0.07%. There was no retained stone, biliary stricture and mortality reported in this series. Conclusion: Complications in laparoscopic cholecystectomy are mainly due to access related and intraoperative and have their own characteristics.. CBD transaction, CHD injury, Colonic perforations and duodenal perforations were the major complications requiring conversion to open procedure except duodenal perforation which was dealt laparoscopically. Conversion to open procedure should not be considered as a complication. J Bangladesh Coll Phys Surg 2023; 41: 75-81